Radical approach to Odontogenic Keratocyst - report of two cases - Rajshekhar Halli; Uma Mahindra; Yogesh Kini; Saurab Bither (Wolters Kluwer Medknow Publications, 2007)
The odontogenic keratocyst has been the subject of great interest ever since Philipsen introduced the term in 1956. Investigations continue into the lesion's pathologic classification, diagnosis and biologic behavior. Considerable controversy exists regarding the proper management of these lesions - conservative or aggressive?. Here we report two cases of large odontogenic keratocysts of the mandible which were treated by aggressive surgical approach.